GTS-21 reduces microvascular permeability during experimental endotoxemia - Schmidt, Karsten; Bhakdisongkhram, Sukanya; Uhle, Florian; Philipsenburg, Christoph; Živković, Aleksandar; Brenner, Thorsten; Motsch, Johann; Weigand, Markus A.; Hofer, Stefan (Microvascular research, 2018)
Introduction: No effective pharmacological therapy is currently available to attenuate tissue edema formation due to increased microvascular permeability in sepsis. Cholinergic mediators have been demonstrated to exert anti-inflammatory effects via the α7 nicotinic acetylcholine receptor (α7nAChR) during inflammation. GTS-21, a partial α7nAChR agonist, is an appealing therapeutic substance for sepsis-induced microvascular inflammation due to its demonstrated cholinergic anti-inflammatory properties and its favorable safety profile in clinical trials. This study evaluated the effect of GTS-21 on microvascular permeability and leukocyte adhesion during experimental endotoxemia. Methods: Male Wistar rats (n=60) were anesthetized and prepared for intravital microscopy (IVM). Sevoflurane inhalation combined with propofol (10mg/kg) and fentanyl (5μg/kg) was used for anesthesia induction, followed by continuous intravenous anesthesia with propofol (10-40mg/kg/h) and fentanyl (10μg/kg/h). The rat mesentery was prepared for evaluation of macromolecular leakage, leukocyte adhesion and venular wall shear rate in postcapillary venules using IVM. Following baseline IVM recording, GTS-21 (1mg/kg) was applied simultaneously with, 1h prior to and 1h after administration of lipopolysaccharide (LPS, 5mg/kg). Test substances (crystalloid solution, LPS, GTS-21) were administered as volume equivalent intravenous infusions over 5min in the respective treatment groups. The consecutive IVMs were performed at 60, 120 and 180min after the baseline IVM. The systemic inflammatory response was evaluated by measuring TNF-α levels after the 180min IVM. Results: Microvascular permeability was significantly reduced in animals treated with GTS-21 simultaneously and 1h after induction of endotoxemia. Leukocyte adhesion, venular wall shear rate and TNF-α levels were not affected by GTS-21 treatment compared to the untreated endotoxemic animals. Conclusion: GTS-21 has a protective effect on microvascular barrier function during endotoxemia. Considering its anti-inflammatory efficacy and safety profile, its clinical use might prove beneficial for the treatment of capillary leakage in sepsis therapy.